Alienational Normlessness, Isolation, and Estrangement: A Neo-Thomistic Approach - Schmidt, Kenneth A. (Journal for the sociological integration of religion and society, 2012)
Most modern research in social alienation was based upon the factors identified by Seeman (1959, 1967, 1971, 1975, and 1983) as powerlessness, meaninglessness, normlessness, isolation, estrangement, and cultural estrangement. Postmodernism reevaluated and redefined the factors within the postmodern paradigm. It was observed neither set of definitions included a spiritual component. It was proposed a redefinition of the self, as individual and personality, within the NeoThomist position of Jacques Maritain could assist researchers of social alienation in a deeper understanding of the alienational factors of normlessness, isolation, and estrangement.